Beginning Drupal - Redding, Jacob (Jacob E.) (Indianapolis, IN : Wiley Pub., 2010)
Presents information on creating and managing a Web site with Drupal.--
"Wrox programmer to programmer"--Cover.
Includes index.
Keywords: Drupal (Computer file); Drupal (Computer software); Open source software; Web sites -- Management; Open source software; Web sites -- Design